LEGAL REVIEW OF THE PROVISIONS OF ARTICLE 97 OF THE KHI ON THE DIVISION OF JOINT PROPERTY BASED ON THE CONCEPT OF BENEFIT - M. Arif Sani; Mhd Azhali Siregar; Andoko, Andoko (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Article 97 of the KHI regulates the division of joint property after divorce, which states "a divorced widow or widower is each entitled to half of the joint property as long as it is not specified otherwise in the marriage agreement." The concept of benefit in this case refers to a fair and mutually beneficial division, namely dividing joint property equally between husband and wife, unless there is an agreement that stipulates otherwise. This study examines the legal review of the provisions of Article 97 of the Compilation of Islamic Law on the division of joint property from the perspective of the concept of benefit. Article 97 of the KHI stipulates that a divorced widow or widower is each entitled to half of the joint property as long as it is not specified otherwise in the marriage agreement. A legal-normative approach is used to analyze how this provision on the division of joint property can be reviewed based on the principle of legal benefit. The results of the study indicate that the application of a rigid division of joint property with a 50:50 proportion does not always reflect substantive justice. The concept of benefit (maslahah) in Islamic law provides flexibility to consider the contribution of each party, the economic conditions after the divorce, and responsibility towards children. This study concludes the need for reinterpretation of Article 97 of the KHI by considering the aspect of benefit to fulfill the objectives of Islamic law in realizing justice and welfare for the parties in accordance with the contemporary socio-economic context.